Adrenocortical carcinoma with inferior vena cava tumor thrombus found during surgery. Issue 5 (3rd June 2022) - Nabeshima, Yuta; Yamashita, Shimpei; Deguchi, Ryusuke; Iwamoto, Ryuta; Warigaya, Kenji; Koike, Hiroyuki; Kikkawa, Kazuro; Kohjimoto, Yasuo; Murata, Shinichi; Hara, Isao
Abstract : Introduction: The safety and efficacy of minimally invasive approaches for adrenocortical carcinoma with inferior vena cava tumor thrombus have not yet been established. We report a case of large adrenocortical carcinoma with inferior vena cava tumor thrombus found perioperatively which required conversion from a laparoscopic to an open procedure. Case presentation: A 71‐year‐old woman with right‐side 10‐cm diameter adrenocortical carcinoma was scheduled for laparoscopic adrenalectomy. The operation was converted to open surgery, however, because inferior vena cava tumor thrombus, which was not detected by preoperative imaging modalities, was found during surgery. Conclusion: In patients with large adrenocortical carcinoma, the possible presence of inferior vena cava thrombus should be considered when selecting surgical procedures.